BULLYING:: CURRENT ISSUES OF COMMISSIONING AND CARRYING OUT OF EXPERT PSYCHOLOGICAL EVIDENCE IN COURT - O. Khodanovych, Vitalii; V. Khodanovych, Olesia; O. Smirnova, Valeriia; Yu. Ponomarenko, Anna (Revista Gênero e Interdisciplinaridade, 2020)
The relevance of the problem under research is due to a significant increase in the number of forensic psychological examinations during considering administrative cases and criminal proceedings in issues of bullying, the conduct of which clearly demonstrates the presence of a number of defects in the theoretical justification of this type of examination. The purpose of the study is to try to solve the problems of forensic psychological examination of bullying, the need for which arises in administrative and criminal proceedings. The methodological basis of forensic psychological examination of bullying is made up of general psychological scientific principles: termism, development of the human psyche in the unity of its consciousness and activity, systematic nature, which involves the study of mental activity as a whole. The study found that the current stage of development of forensic psychological examination of bullying is characterized by unequal treatment of both lawyers and psychologists. Forensic psychological examination of bullying requires the development of an appropriate methodology for its implementation, based on the use of a significant number of general psychological and special methods. The materials in this article may be useful for law enforcement personnel, legal proceedings, psychology specialists, and research workers focused on conducting research on bullying problems.